The Catalytic Synthesis of Aza-Sulfur Functional Groups - Wei, Ming-Kai; Willis, Michael C. (Synthesis, 2024)
Sulfur-containing compounds are found in myriad applications. Sulfones and sulfonamides are the most common functional groups used in medicinal and agrochemical endeavours. Isosteres of these functional groups, for example, sulfoximines and sulfonimidamides, are emerging functionalities, and they are increasingly common in the relevant patent literature. However, in general, the associated synthetic routes still have limitations, including the use of harsh reaction conditions and highly reactive reagents. A variety of catalytic reactions that employ a diverse range of substrate classes have been developed to address these issues. This short review highlights recent catalytic syntheses of aza-sulfur compounds, which we hope will open new directions in discovery chemistry.1 Introduction2 Reactions of N-Sulfinylamines3 Reactions with Sulfenamides4 Reactions with Sulfinates5 Reactions with Sulfinamides6 Reactions with Other Aza-Sulfur Compounds7 Conclusion
Keywords: sulfur chemistry; metal catalysis; photochemistry; asymmetric catalysis